Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s13075-015-0516-6
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab in patients with active rheumatoid arthritis after treatment with tumor necrosis factor α inhibitors: findings with up to five years of treatment in the multicenter, randomized, double-blind, placebo-controlled, phase 3 GO-AFTER study

Abstract: IntroductionThe aim of this study was to assess long-term golimumab therapy in rheumatoid arthritis (RA) patients who discontinued previous tumor necrosis factor-α (TNF)-inhibitor(s).MethodsPatients enrolled into this multicenter, randomized, double-blind, placebo-controlled study of active RA (≥4 tender, ≥4 swollen joints) received placebo (Group 1) or golimumab 50 mg (Group 2) or 100 mg (Group 3) injections every 4 weeks. Patients in Groups 1 and 2 with inadequate response at week 16 escaped to golimumab 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
6
34
0
3
Order By: Relevance
“…No new safety signals were observed over the course of the 7-year treatment period, with AE ERs comparable to other long-term anti-TNF studies [2124]. AEs were consistent with other long-term evaluations of CZP in combination with MTX given as a 200 mg dose every 2 weeks (Q2W) [2527].…”
Section: Discussionsupporting
confidence: 82%
“…No new safety signals were observed over the course of the 7-year treatment period, with AE ERs comparable to other long-term anti-TNF studies [2124]. AEs were consistent with other long-term evaluations of CZP in combination with MTX given as a 200 mg dose every 2 weeks (Q2W) [2527].…”
Section: Discussionsupporting
confidence: 82%
“…In RA, three OLE studies13,44,45 presented data on per sistence to golimumab after 256 weeks (approximately five years). In biologic-naive patients, GO-BEFORE enrolled methotrexate-naive patients;45 and GO-FORWARD enrolled patients with inadequate response to methotrexate 13.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to overall AE and SAE, the incidence of AE of special interest (serious infections including opportunistic infections and TB, deaths, malignancies, and demyelination) per 100 pt-yrs was determined. Patient retention was substantial, with about 60% of patients with RA, 69% with PsA, and 72% with AS completing 5 years of followup, reflecting the sustained efficacy observed through up to 5 years of GOL treatment 10,14,17,21,24 . This retention, which compares favorably with 5-and 10-year drug survival rates for ETN 29 and ADA 30 , respectively, allowed for the analysis of 2228 patients with a mean of 203 weeks of GOL safety followup.…”
Section: Variablesmentioning
confidence: 99%
“…No further ethical approval was required to conduct the additional data analyses reported herein. Patient entrance criteria and study designs for each trial have been reported [8][9][10][11][12][13][14][15][16][17]18,19,20,21,22,23,24 and are summarized in Table 1. Additionally, further details of each trial are available at clinicaltrials.gov (GO-BEFORE: NCT00264537, GO-FORWARD: NCT00264550, GO-AFTER: NCT00299546, GO-REVEAL: NCT00265096, GO-RAISE: NCT00265083).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation